2006
DOI: 10.1002/art.22163
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of giant cell arteritis using induction therapy with high‐dose glucocorticoids: A double‐blind, placebo‐controlled, randomized prospective clinical trial

Abstract: Objective. Glucocorticoid (GC) therapy for giant cell arteritis (GCA) is effective but requires prolonged administration, resulting in adverse side effects. The goal of the current study was to test the hypothesis that induction treatment with high-dose pulse intravenous (IV) methylprednisolone permits a shorter course of therapy.Methods. Twenty-seven patients with biopsyproven GCA were enrolled in a randomized, doubleblind, placebo-controlled study to receive IV methylprednisolone (15 mg/kg of ideal body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
23

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 303 publications
(176 citation statements)
references
References 31 publications
0
153
0
23
Order By: Relevance
“…In GCA patients receiving high-dose oral GCs, myopathy was listed as an AE in 3/39 patients in a 2-year trial [ 43 ] but in 0/27 patients in a 78-week trial [ 44 ]. Yet in a third trial, 20/21 GCA patients reported 'subjective muscle weakness' [ 45 ].…”
Section: Myopathymentioning
confidence: 99%
“…In GCA patients receiving high-dose oral GCs, myopathy was listed as an AE in 3/39 patients in a 2-year trial [ 43 ] but in 0/27 patients in a 78-week trial [ 44 ]. Yet in a third trial, 20/21 GCA patients reported 'subjective muscle weakness' [ 45 ].…”
Section: Myopathymentioning
confidence: 99%
“…Initial therapy for active Takayasu arteritis and active giant cell arteritis should be corticosteroids at a high dose (prednisone 40 to 60 mg daily at initiation or its equivalent) to reduce the active inflammatory state. 66,67 (Level of Evidence: B) 2. The success of treatment of patients with Takayasu arteritis and giant cell arteritis should be periodically evaluated to determine disease activity by repeated physical examination and either an erythrocyte sedimentation rate or C-reactive protein level.…”
Section: Class Imentioning
confidence: 99%
“…metilprednizolon tedavisi konvansiyonel prednizolon 40 mg/gün tedavisi ile sa¤lamas› aç›-s›ndan karfl›laflt›r›lm›flt›r. [52] Çal›flmada, biyopsi ile kan›t-lanm›fl DHA tan›l› 27 hasta randomize i.v. metilprednizolon (15 mg/kg günde 3 doz) veya i.v.…”
Section: Tedaviunclassified